Las prácticas evaluativas del profesorado de francés como lengua extranjera en secundaria (Investigaciones) - Kuok Wa, Chao Chao (2022)
This exploratory research with 58 French teachers in secondary education in Costa Rica aims to describe their assessment practices used in French as a foreign language class. An online questionnaire was used as an instrument for data collection. As the main result, the teachers have a traditional conception of assessment. In addition, the instrumentation used to assess their students is exams, dayto- day work, or homework. Furthermore, the teachers rely on the courses' objectives and contents to assess their students. Finally, assessment is an individualized practice for this group of teachers.